Sygnał klimatyczny w przyroście radialnym wybranych iglastych gatunków drzew w Leśnym Zakładzie Doświadczalnym Rogów - Bijak, Szymon (Leśne Prace Badawcze, 2013)
I present dendroclimatological analysis of coniferous tree species growing under the same environmental conditions in the WULS-SGGW Forest Experimental Station in Rogów (51°49′ N, 19°53′ E, ca. 190 m a.s.l). The study focuses on silver fir, European larch, Scots pine and Douglas fir. For each species, tree-ring width and annual sensitivity chronologies were developed for the period 1931–2010. Analysed species show considerable similarity of their radial increment course (GLK up to 67%, the t-value of 3,5–9,5). The relationship obtained for of the influence of climate conditions on radial growth of these species is typical of the relationships reported from other locations in lowland Poland. Late winter and early spring temperature, especially during February-March, is the main factor affecting tree-ring formation. The general relationship demonstrates that this seasonal thermal limitation operates at an inter-regional and interspecific level in determining the growth of coniferous tree species in Poland. Whereas, the dependence of these species on precipitation is much less significant.